Effect of early versus deferred antiretroviral therapy for HIV on survival. - Kitahata, Mari M; Gange, Stephen J; Abraham, Alison G; Merriman, Barry; Saag, Michael S; Justice, Amy C; Hogg, Robert S; Deeks, Steven G; Eron, Joseph J; Brooks, John T; Rourke, Sean B; Gill, M John; et al. (The New England journal of medicine, 2009)
The optimal time for the initiation of antiretroviral therapy for asymptomatic patients with human immunodeficiency virus (HIV) infection is uncertain.
Keywords: Adult; Anti-Retroviral Agents; CD4 Lymphocyte Count; Confounding Factors (Epidemiology); Drug Administration Schedule; Female; HIV; HIV Infections; Humans; Male; Middle Aged; Proportional Hazards Models; Risk; RNA, Viral; Survival Analysis